Self-Reflections on Differentiation: Understanding How We Teach in Higher Education - Nykela Jackson; Lesley Evans (Networks: An Online Journal for Teacher Research, 2017)
Teachers are called to accommodate the individualized learning needs of a wide range of students. To support prospective and current teachers with this challenge, it is imperative to help them not only understand the theory of differentiated instruction, but how to implement it into practice. Building upon past research in the realm of higher education, this study sought to identify the past teaching experiences and expectations of two former K-12 teachers that formed the philosophy and practices that they bring to teacher preparation courses. Framed by interview questions used in past research with faculty, the two researchers self-reflected on their own practices to consider how they related to various differentiation approaches and their individual transitions to higher education. Three themes emerged through the reflection of the two junior faculty members: differentiated instruction is student centered and student involved; assessment is intertwined with instruction; and differentiated instruction is needed in teacher preparation programs.
Keywords: differentiation; higher education; self-reflection; instruction